Azidophenantridinium compounds as photoaffinity labels of cholinergic proteins - Stengelin, Siegfried; Walther, Christian; Hucho, Ferdinand (Biochimica et biophysica acta, 1978)
The synthesis of diazidopropidium and diazidoethidium is described. The applicability of these compounds as photoaffinity labels for cholinergic proteins has been investigated: diazidopropidium inhibits neuromuscular transmission. This inhibition is reversible if the compound is applied in the dark but becomes irreversible after irradiation with white light. Inhibition is accompanied by a disappearance of miniature endplate potentials. Electrophysiological analysis of this effect indicates that diazidopropidium acts postsynaptically by blocking the acetylcholine receptors. At the molecular level the action of diazidopropidium and diazidoethidium on acetylcholinesterase has been investigated: both compounds appear to bind to a peripheral acetylcholine binding site of this enzyme. Binding of 125I-labeled α-neurotoxin from Naja naja siamensis to purified membranes from Torpedo californica electric tissue rich in acetylcholine receptors is diminished after incubation and irradiation with diazidopropidium. About half of the toxin binding sites appear to be blocked by the photoaffinity label.